The power of points in presentation - Girija Kartha (Indian Association of Preventive and Social Medicine, 2011)
Many topics came to my mind for this editorial, mostly health and medicine related, obviously. But I thought "why not break the track" and write about one of the most "used and abused tools" of presentations, of present day. I had chances to attend many seminars and conferences and no presenter comes without a PPT, which means, a PPT is a part of our life, be it Medicine, Business, or any other profession, for that matter. As professionals, we would be required to know the effective use of PPT. Just having a basic knowledge of PPT which, to many seems to suffice, is actually not enough, which is why I used the terms the most "used and abused tool". ....